THE EFFECT OF COMPARISON OF DIFFERENT STARCH SOURCES TO CONSUMER ACCEPTANCE AND QUALITY OF ANALOG RICE FROM SNAKEHEAD FISH (Channa striata) - Riski Abadi; Syahrul Syahrul; N. Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis research was aimed: 1) to determine the ratio of different blended starch sources (sago flour, brown rice and corn) to the quality of the snakehead fish analog rice produced; 2) to determine the characteristics of snakeheadfish analog rice produced based on organoleptic value, nutritional value and total aerobic bacteria (TPC). This research was conducted by an experimental method. The research design used was a completely randomized design (CRD) of one factor, namely the source of starch differs from 4 levels of formulation. The results showed that the F4 was the best treatments with sago flour (60%), brown rice flour (20%), corn flour (20%) and snakeheadfish flour (10%) with brownish colored characteristics, typical odor of rice, the hard and solid, delicious flavor with moisture content (8.19%), ash content (1.32%), fat content (0.18%), protein content (9.30%), carbohydrate content (80.95%) and crude fiber (0.14%) and total bacterial colonies 2.4 x 103colonies/g.Keywords: Analog rice, snakehead fish, starch source